Effect of saline drainage water on performance of denitrification bioreactors - Sasan Faramarzmanesh (IWA Publishing, 2021)
Excessive use of nitrate fertilizers in agriculture causes harm to humans and the environment. The most suitable nitrate removal process is heterotrophic biological denitrification. The purpose of the present study was to evaluate the performance of three shapes of denitrification bioreactors: triangular, rectangular and semicircular. The main element that was used to remove nitrate was beech woodchips. The concentration of inlet nitrate was 75 mg/l and the salinity of the solution was 1 ds/m and 5 ds/m, for a period of six months. The results showed that the efficiency of the triangular bioreactor with a salinity level of 1 ds/m was 90%, which is more efficient than the rectangular and semicircular bioreactors with performances of 55.8% and 53.8%, respectively. The results also indicated that at a salinity level of 5 ds/m, the semicircular bioreactor with a performance of 50.8% inlet nitrate removal was the best of the three shapes of bioreactors tested, the efficiencies of the triangular and rectangular bioreactors were 49.9% and 48.6% respectively. Also, it was observed that at the salinity level of 1 ds/m, a high hydraulic retention time had a high positive effect on denitrification, on the other hand at the salinity level of 5 ds/m, there was better performance of denitrification if the hydraulic retention time was lower.